Using Break Quantities for Tactical Optimisation in Multistage Distribution Systems - Marcel J. Kleijn; Rommert Dekker (Tinbergen Institute, 1997)
In this chapter we discuss a tactical optimisation problem that arises in a multistage distribution system where customer orders can be delivered from any stockpoint. A simple rule to allocate orders to locations is a break quantity rule, which routes large orders to higher-stage stockpoints and small orders to end-stockpoints. A so-called break quantity determines whether an order is small or large. We present a qualitative discussion on the implications of this rule for the marketing process, and a qualitative and quantitative analysis on the implications for the transportation and inventory costs. Furthermore, wepresent a case study for a company that implemented a break quantity rule. Finally, in the last section the main results are summarised.
Keywords: 330; Distribution systems; inventory; transportation; marketing; break quantity rule